PARE0009 "Collective Osteoporosis Workgroup": A Collective to Throw Back the Tracking of the Osteoporosis. (10th June 2014) - Dachicourt, J.-N.; Cortet, B.; Grange, L.; Blain, H.; Guggenbuhl, P.; Dreux, C.; Tremollières, F.; Thomas, T.
Abstract : Background: The osteoporosis heavy weighs in the public health expenses, directly (care bound to fractures) and indirectly (associated cost to the reduction of autonomy and handicap). In overcoming years, an upsurge of fractures number bound to osteoporosis will grow up in France. Indeed, the life expectancy increases and the abandonment of the hormonal treatments for menopause treatment amplifies the risk of osteoporosis and fractures. Objectives: Besides, various factors contribute to a stagnation of the yearly number of Dual-energy X-ray absorptiometry (DXA) repaid in France. In 2012, to throw back the tracking of the osteoporosis and the prevention of fractures, the AFLAR (French league against rheumatism) decided to create a "Collective Osteoporosis Workgroup" regrouping various actors concerned by osteoporosis. Methods: This collective group met in 2012 and 2013 to analyse the tendencies in term of impact of the osteoporosis and osteoporotic bones fractures, as well as to identify the brakes for the screening of this pathology. A strong work of synthesis of all present scientific literature world database, permitted the production of a succeeded production of a containing synthesis document and led to incentive measures that will be defended by the Collective to the french stakeholders. Results: This collective group asks for the setting up of three measures. – The repayment of the DXA exam for every woman of more than 60 years old. Simplify the access to the DXA exam is an efficient measure in terms of cost: reducing the repayment (valued to €48, 5 M, treatments include) is weak regarding to the achieved savings which could be done in reducing the number of fractures (of €107 to €121 M on ten years, according to the studies); – The setting up of information and sensitization campaigns for the prevention and the tracking of the osteoporosis for general public and the health professionals; – Give a fast assessment questionnaire of osteoporosis risks factors (IOF or GRIO questionnaire) during mammography exam to every woman of more than 50 years old. For the World Osteoporosis Day, AFLAR led some actions to make know the measures defended by this collective group: sensitization of deputies and stakeholders by a flash mob took place in front of French National Assembly, launching at the same time a press campaign. Conclusions: In the next months, the "Collective Osteoporosis Workgroup" is going to continue its mobilization and advocacy work to defend the measures that it recommends and, more generally, to boost the efforts of prevention and tracking on osteoporosis. Campaigns of sensitization will be led towards Public and People suffering of osteoporosis risks, as well as towards the health decision-makers in order to lead to have these 3 main proposal measures applied. Regarding to the increase of the rate of hospitalizations for hip fracture, particularly for 85 years old people and more (+ 7, 5% from 2008 to 2009), it is essential to increase the effort of preventing and tracking osteoporosis. Using this advocacy action will help AFLAR to reverse this tendency. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5929